Transactional and transformational leadership style towards students' achievement in Pahang / Joeaiza Juhari, Khairunnisa Othman and Maryam Jameelah Hashim - Juhari, Joeaiza; Othman, Khairunnisa; Hashim, Maryam Jameelah (2012)
The leadership theories have been extensively discussed and applied in numerous studies. Teacher leadership for instance is a growing area but most of the studies or research conducted by scholars typically involved leaders within an organization such as school principal and not specifically on the teachers themselves. The main purpose of this research is to determine which leadership styles affect and has the greatest influence on students' achievement at school. Participants in the research included 100 respondents from school principals and teachers in secondary school in Jerantut District in Pahang. These participants were given structured questionnaires and formal interviews with several school teachers were done. Multifactor Leadership Questionnaire (MLQ Form 5X) was used to measure leadership styles practiced by these teachers. The completed questionnaires was statistically analyzed using SPSS Version 17. The findings obtained from the analysis exhibited that most of the respondents were female teachers between the ages of 41 to 45 years and have served for 9 years in educational fields. Both analysis used by researchers found that transactional leadership is very strongly correlated with students' achievements and also has the greatest influence towards students' achievements in Jerantut, Pahang. Besides, Cronbach Alpha for all variables chosen were good and acceptable. It means, all the items in a set were positively correlated with one another.